Developing a food safety consumer experience scale: Qualitative insights from Bangladesh, Ethiopia, and Vietnam - Isanovic, S.; Alonso, Silvia; Frongillo, E.A.; Parvin, A.; Gazu, Lina; Nguyen, Phuong Hong; Leroy, Jef L. (Elsevier, 2025)
Objectives: Unsafe food contributes to 600 million cases of foodborne illness and 420,000 deaths annually. Existing methods used to evaluate food safety risks overlook consumers’ perspectives coming from their everyday experiences that influence their food choices. Our objective was to develop a cross-culturally appropriate and user-friendly scale to assess consumers’ experiences related to food safety in low- and middle-income countries. This study identified the constructs that constitute the experiences of food safety that the scale should reflect.